Formulasi dan Evaluasi Masker Hyrogel Ekstrak Etanol Pegagan (Centella Asiatica (L). Urb) Sebagai Antiaging dengan Variasi Basis Carbopol dan HPMC - Vina Purnamasari M; Nurlina Nurlina; Anita Sari Anwar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Gotu kola ethanol extract (Centella asiaticaI (L)urb.) has very strong antioxidant activity with an IC50 value of 20.43 μg/ml which can be utilized in the development of pharmaceutical or cosmetic preparations. The purpose of this study was to formulate and evaluate a pharmacologically stable preparation of hydrogel antiaging mask of gotu kola ethanol extract (Centella asiaticaI (L)urb.). The research design used by varying the concentration of carbopol and HPMC was then carried out physical evaluations such as organoleptis, homogeneity, ph measurement, viscosity and flow type tests, adhesion tests, dispersion tests, weight and size tests of hydrogel masks, inflating power tests and shrinkage tests and stability tests. The evaluation results showed that gotu kola ethanol extract (Centella asiaticaI (L)urb.) that met the pharmaceutical stability test was formula 2 with a carbopol concentration of 1.25% and HPMC 2.25%.